Kidney Organoids as a Novel Platform to Evaluate Lipopolysaccharide-Induced Oxidative Stress and Apoptosis in Acute Kidney Injury - Zhang, Weitao; Qi, Ruochen; Li, Tingting; Zhang, Xuepeng; Shi, Yi; Xu, Ming; Zhu, Tongyu (Frontiers in Medicine, 2021)
Sepsis-associated acute kidney injury (SA-AKI) is a life-threatening syndrome. Lipopolysaccharide (LPS) is a widely used inducer for modelling SA-AKI both in vivo and in vitro. However, due to the innate complexity of kidney architecture, the mechanisms underlying the pathogenesis of SA-AKI, as well as those involved in LPS-induced kidney injury remain to be clarified. Kidney organoids derived from human pluripotent stem cells (hPSCs) act as a model of multiple types of kidney cells in vitro and eliminate potential confounders in vivo. In the current study, we established LPS-induced kidney injury models both in vivo and using human kidney organoids. Kidney function, pathological changes, and markers of oxidative stress were evaluated with/without the presence of methylprednisolone (MP) treatment both in vivo and in vitro. The extent of LPS-induced oxidative stress and apoptosis in kidney organoids was further investigated in vitro. LPS-induced acute kidney injury in mice, together with pathological changes and increased oxidative stress, as well as enhanced apoptosis in kidney cells were evaluated. These phenomena were ameliorated by MP treatment. Experiments in kidney organoids showed that the LPS-induced apoptotic effects occurred mainly in podocytes and proximal tubular cells. Our experiments demonstrated the efficacy of using kidney organoids as a solid platform to study LPS-induced kidney injury. LPS induced oxidative stress as well as apoptosis in kidney cells independently of changes in perfusion or immune cell infiltration. MP treatment partially alleviated LPS-induced injury by reducing kidney cell oxidative stress and apoptosis.